PHYSIOLOGICAL CONTROL METHODS AND FUNCTIONAL ASSESSMENT TECHNIQUES IN SPORTS MEDICINE (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive overview of the scientific and theoretical foundations as well as the practical applications of physiological control methods and functional assessment techniques in sports medicine. Physiological control methods serve to regularly monitor functional changes in the athlete’s body, determine their level of adaptation to physical loads, and individualize the training process. Functional assessment methods, in turn, make it possible to evaluate the athlete’s level of preparedness by analyzing heart rate, blood pressure, respiratory activity, muscle performance, and recovery processes.